THE STUDY OF URBAN SPRAWL CASE STUDY : TANJUNG MORAWA DISTRICT, DELI SERDANG REGENCY - Kusriyadi Kusriyadi (Jurnal Teknologi Terapan and Sains 4.0, 2021)
Tanjung Morawa District is located in Deli Serdang Regency, which is directly adjacent to Medan City. It is a strategic area from economic growth importance point of view and potentially to grow fast. It has the chance for urban sprawl when it is not anticipated early. Therefore it is necessary to know whether urban sprawl has occurred in the study area, how much of the factors causing urban sprawl to affect the study area when it occurred, and which areas are mostly affected. This research study uses the overlay method to determine land use changes from year 2005 to 2015, then performs calculations to determine how much urban sprawl factors affect the study area using the Analytical Hierarchy Process. The conclusion of the study is that urban sprawl has occurred in Tanjung Morawa District with low typology, the influencing factors are accessibility 0.35, public services 0.19, land characteristics 0.15, land owner characteristics 0.15, the existence of regulations governing spatial planning 0.09, and developer initiatives 0.07, area that affected the most is the village of Tanjung Morawa B.Keywords : Urban sprawl, Overlay, Analytical Hierarchy Process